Pengaruh Pelayanan Kesehatan Ibu dan Anak terhadap Peningkatan Kesehatan Masyarakat (Studi pada Pusat Kesehatan Masyarakat Kibin Kecamatan Kibin Kabupaten Serang) - Rosilawati, Rosilawati (Universitas Serang Raya, 2018)
This study aims to determine whether there is a significant influence between maternal and child health services on improving community health. This research is quantitative, as for the population and samples taken as many as 78 respondents with a randomly stratified random sampling. Instrument research data uses three types of tools, namely questionnaires using the Likers scale model. The questionnaire was prepared with the construction of various data analysis theories carried out at the level of 95%. The results were significant as long as the hypothesis existed. So that the results of this study tell that the variables of maternal and child health services can influence the level of public health.